Increasing Interest in Learning Mathematics with the Make-A-Match Learning Model for Class II Students at Al-Azhar Gampengrejo Islamic Elementary School - Amalia, Diana; Khoiruddin, M Arif (Noumerico: Journal of Technology in Mathematics Education, 2023)
Mathematics has an important role in life, especially in the development of technology and science. Given the importance of mathematics, this subject is taught in schools, starting from early childhood education to high school, including in tertiary institutions. For some students, mathematics at school is a subject that is considered arduous and frightening. The teacher's role is important and necessary to increase students' interest in learning, especially in mathematics. Teachers are required to be precise in using effective models and being able to influence students to actively participate in the learning process to the fullest and increase their learning outcomes. This study aims to increase students' interest in learning with the Make a Match learning model which focuses on students interacting and collaborating in developing their knowledge through the concept of playing while learning. The method used in this study uses classroom action research. Starting from planning, implementation, observation, and reflection. The use of make-a-match in mathematics with the mathematics of division, and multiplication with numbers, as well as the introduction of flat shapes and their results can increase student learning interest by 88.8% from previously only 58.8% by using lectures.